Review of host-plants of Tuta absoluta (Meyrick) for a better management of populations in West Africa - (:unkn) unknown (My University, 2022)
Tuta absoluta (Meyrick) is an invasive pest species originating from South America of great importance for Solanaceae crops. It is currently present in most African countries and was reported in Senegal in 2012, where it is responsible for significant damage on tomato. Because of the significant role of alternative host-plants in the maintenance, dynamics and management of T. absoluta populations, a review of the literature was undertaken to inventory host-plants of the species. Seventy (70) bibliographical references of various types and sources were then consulted. They allowed us to identify sixty-eight (68) botanical species distributed in 11 families, namely Solanaceae (66,17%), Fabaceae (7,35%), Chenopodiaceae (5,88%), Amaranthaceae (4,41%), Malvaceae (2,94%), Asteraceae (2,94%), Convolvulaceae (2,94%), Cucurbitaceae (2,94%), Euphorbiaceae (1,47%), Poaceae (1,47%) et Geraniaceae (1,47%). The vernacular names of some species are given in French, Pulaar, Wolof and/or Serer to allow a better dissemination of information to local producers.
Keywords: African Research